1996
DOI: 10.1002/crat.2170310302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supersaturation and Temperature on the Growth Morphology of Ammonium Oxalate Monohydrate Crystals Obtained from Aqueous Solutions

Abstract: The cxpcrirriental rcsults of a study of the effect of supcrsaturation and temperature on the growth morphology of ammoniuni oxalatc monohydrate [ (NH&C201 . H 2 0 ; AO] single crystals obtained from aqueous soliltions at 30 and 40 "C and supcrsaturation up to 9% arc presented. The observations arc analyscd in terms of theoretical morphology, growth models and attachment cncrgy for growth imits in steps of growing faces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The authors studied the growth kinetics [1] and growth morphology [2] of ammonium oxalate monohydrate [(NH 4 ) 2 C 2 O 4 ·H 2 O; AO] crystals from "pure'' aqueous solutions as a function of supersaturation and temperature. It was observed that most of the faces appearing in the morphology are F faces, and that the general dependence of growth rate R of different faces of crystals on supersaturation σ may be described satisfactorily by the surface diffusion model of Burton, Cabrera and Frank (BCF model) [3,4] and by a model involving complex source of cooperating screw dislocations [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The authors studied the growth kinetics [1] and growth morphology [2] of ammonium oxalate monohydrate [(NH 4 ) 2 C 2 O 4 ·H 2 O; AO] crystals from "pure'' aqueous solutions as a function of supersaturation and temperature. It was observed that most of the faces appearing in the morphology are F faces, and that the general dependence of growth rate R of different faces of crystals on supersaturation σ may be described satisfactorily by the surface diffusion model of Burton, Cabrera and Frank (BCF model) [3,4] and by a model involving complex source of cooperating screw dislocations [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…At low supersaturations the steps of the macrospirals on the as-grown faces of the crystals grown both from solutions without impurities and in the presence of the impurities were oriented along low-index crystallographic directions, i.e. the macrospirals had a tendency to be polygonal [2,6]. With increasing supersaturation the macrospirals become rounded and better developed [6].…”
Section: Introductionmentioning
confidence: 96%
“…It was observed [2] that most of the faces appearing in the morphology are F faces and that macrospirals and growth hillocks appear on these faces. The authors also investigated [3][4][5][6] the effect of Cu(II), Fe(III) and Cr(III) ions on the growth of different faces of AO crystals.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations